Analisa Penggunaan Abu Vulkanis Gunung Kelud Sebagai Campuran Agregat Halus pada Beton Normal dengan Mutu Fc’=22,5 MPa - Utomo, Sugeng; Ningrum , Diana; Rasidi, Nawir (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
In structure construction, concrete holds important part. Normal concrete is composed of sands, cement, gravels and water. In general, sands that used to make concrete is mostly came from Lumajang, East Java and because of that the price of it is increased over time. So it is necessary to do research about another alternative for the soft aggregates. Volcanic ash from Kelud Mountain can be one of the solve that can be used to be mixed with Lumajang?s sand. This research determines the effect of the volcanic ash as a partial substitute of the Lumajang?s sand with compressive strength as the comparison. Speciments that used in this research are concrete cylinders with diameter of 150 mm and height of 300 mm. Number of test speciments for each variation are 3 speciments. The results showed that at the 0% substitute variation obtained 29.90 MPa of the average compressive strength, for the 5%, 10% and 15 % obtained 30.02 MPa, 24.63 MPa and 27.54 MPa of the average compressive strength. It shows that the maximum average compressive strength is at the 5% substitute variation at 30.02 MPa. It shows that at 5% variation the compressive strength is increased compared with 0% and then at 10% it is decreased and start to increased again at 15% substitute variation.